2019
DOI: 10.15171/joddd.2019.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hounsfield Unit in CT scan with the Gray Level in cone-beam CT

Abstract: Background. The present study was undertaken to compare the Hounsfield Unit (HU) in computed tomography (CT) with the gray level in CBCT in human tissues. Methods. In this study, 25 different soft and hard tissues were evaluated in 21 patients. CBCT images were taken with Newtom VGi machine (Verona, Italy) and CT images were prepared with Somatom Sensation unit (Siemens, Germany). The HU values of soft and hard tissues were compared with the gray level values of CBCT images. Results. There was a strong correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 21 publications
2
46
0
5
Order By: Relevance
“…stated that gray scale in CBCT is the standard for measuring bone density before implant treatment, and that this method is recommended because of the lower radiation dose and cost compared to CT scanning. 25 However, Cassetta reported that a conversion ratio must be applied to the VV to more accurately define the bone density with CBCT. 26 …”
Section: Discussionmentioning
confidence: 99%
“…stated that gray scale in CBCT is the standard for measuring bone density before implant treatment, and that this method is recommended because of the lower radiation dose and cost compared to CT scanning. 25 However, Cassetta reported that a conversion ratio must be applied to the VV to more accurately define the bone density with CBCT. 26 …”
Section: Discussionmentioning
confidence: 99%
“…They suggested that CBCT scans are suitable to predict the implant stability and, therefore, help decide whether immediate or early loading of implants should be performed [ 22 ]. CT scans do not appear to have any advantage over CBCT scans in classifying bone quality [ 32 ]. The mean gray values obtained by a CBCT scan and HUs in a CT scan show a strong correlation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT scans do not appear to have any advantage over CBCT scans in classifying bone quality [32]. The mean gray values obtained by a CBCT scan and HUs in a CT scan show a strong correlation [33].…”
Section: Measurements Of Bone Densitymentioning
confidence: 99%
“…When these algorithms will be applied for a cone-beam CT (CBCT), we must convert a gray scale value to a Hounsfield unit value. Some studies have shown a strong linear relationship between Hounsfield units (HU) and gray scale [19,20]. Gray scale is different from HU due to higher noise levels, more scattered radiation, high heel effect, and beam hardening artifacts [21,22].…”
Section: The Problem Of Threshold Value Adapted To Any Ct or A Cone-beam Ctmentioning
confidence: 99%